2016
DOI: 10.18273/revbol.v38n4-2016003
|View full text |Cite
|
Sign up to set email alerts
|

Estratigrafía Del Neógeno Superior Al Sur De La Cuenca Tumaco (Pacífico Colombiano): La Formación Cascajal, Propuesta De Redefinición Litoestratigráfica

Abstract: S.A. 2016. Estratigrafía del Neógeno Superior al sur de la cuenca Tumaco (Pacífico colombiano): la Formación Cascajal, propuesta de redefinición litoestratigráfica. Boletín de Geología, 38(4): 43-60. RESUMENEl conocimiento estratigráfico del relleno sedimentario del segmento onshore de la cuenca de ante-arco Tumaco es poco conocido y los trabajos existentes se fundamentan en el estudio de líneas sísmicas y pozos para la exploración de hidrocarburos, haciendo poco énfasis en las unidades más superficiales. Se p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
0
7
0
2
Order By: Relevance
“…The stratigraphic information was obtained from electrical logs, ditch cutting, and core samples from the Remolino Grande-1 (total depth (TD) 9080'-2767 m), Majagua-1 (TD 14 280'-4352 m), and Tumaco 1-ST-S (TD 1899.6'-579 m) wells. This information was also integrated with data from outcrops located in the Tumaco Bay (e.g., Echeverri et al, 2016), with previous results reported by Suárez (1990) and López-Ramos (2009) and data from the ANH Tumaco 1-ST-P well (Agencia Nacional de Hidrocarburos & Antek, 2013). The well cores and cuttings are stored at the national core repository of Colombia (Litoteca Nacional, Piedecuesta, Santander).…”
Section: Stratigraphy and Seismic Datamentioning
confidence: 85%
See 4 more Smart Citations
“…The stratigraphic information was obtained from electrical logs, ditch cutting, and core samples from the Remolino Grande-1 (total depth (TD) 9080'-2767 m), Majagua-1 (TD 14 280'-4352 m), and Tumaco 1-ST-S (TD 1899.6'-579 m) wells. This information was also integrated with data from outcrops located in the Tumaco Bay (e.g., Echeverri et al, 2016), with previous results reported by Suárez (1990) and López-Ramos (2009) and data from the ANH Tumaco 1-ST-P well (Agencia Nacional de Hidrocarburos & Antek, 2013). The well cores and cuttings are stored at the national core repository of Colombia (Litoteca Nacional, Piedecuesta, Santander).…”
Section: Stratigraphy and Seismic Datamentioning
confidence: 85%
“…Subsequently, Nivia et al (2003) separated the youngest alluvial and deltaic deposits from the Guapi Formation, defining as Cascajal and Curay Members those underlying Pliocene and Miocene sedimentary deposits in the Nariño Department. Echeverri et al (2016) proposed the term Cascajal Formation for the volcanoclastic rocks of the Messinian -Zanclean age reported by Nivia et al (2003) (Figure 2). In contrast, in the northern part of the Tumaco Basin, Aspden (1984) and Aspden & Nivia (1985) proposed to divide the Neogene sedimentary cover into two formations: (i) Mayorquín Formation, composed mainly of mudrocks, and (ii) Raposo Formation, with conglomerates and sandstones.…”
Section: Stratigraphy Of the Tumaco Basinmentioning
confidence: 96%
See 3 more Smart Citations